'The History That Has Made You'. Ego-Histoire, Autobiography and Postcolonial History. Issue 4 (2nd October 2019) - Cole, Anna
ABSTRACT: This article takes inspiration from the methodology of ego-historie, where political or intellectual history, institutional affiliations and research trajectories are interwoven with personal reflection, to make connections between context and content. In his essay on ego-histoire (2014) John Docker writes of the 'marrano-like' figure, the stranger as evoked by Georg Simmel, both inside and outside a group, disturbing it by a kind of abstraction, a freedom to question what others in the group take as given. Here I employ my insider/outsider status as a British migrant and a 'naturalised' Australian to reflect on the ambivalent at best and deliberately ignorant, at worst, relationship between contemporary Britain and postcolonial Australia. As the child of immigrants to Australia, who has returned to the 'mother-country' as an adult, I use aspects of my autobiography to reconsider the dynamics of colonialism and post-colonialism in these two countries.